PEMANFAATAN LIMBAH KULIT NANAS SEBAGAI BAHAN BAKU SABUN CAIR ALAMI: INOVASI PENGOLAHAN LIMBAH DI DESA UJUNG BATU TIMUR - Yanti Nopiani; Yusmarini Yusmarini; Vonny Setiaries Johan; Shanti Fitriani; Emma Riftyan; Nur Hasnah AR; Annisa Nazifa Salman; Jeany Ristia; Bintang Sipartogi Panjaitan; Chandra Gunawan (Jurnal Abdi Insani, 2025)
Pineapple (Ananas comosus) is a nutrient-rich tropical plant often processed into various products. At the same time, its peel waste contains valuable compounds such as bromelain enzyme and ascorbic acid, which are beneficial for skin care. Based on observations by students from the KKN MBKM program at the Faculty of Agriculture UNRI, it was found that the society is very interested in programs that discuss the processing of organic waste using simple methods, in line with the potential for utilizing agricultural product waste in Ujung Batu Timur village. This activity involves utilizing pineapple peel waste as a natural additive in the production of liquid soap through a community service program in Ujung Batu Timur, Rokan Hulu, Riau Province. This community service initiative aims to raise awareness among the community about organic waste management and enhance skills in creating economically valuable products. The methods used include socialization and practical training on making liquid soap from pineapple peel extract. The community service activities are carried out in three stages: preparation, implementation, and evaluation held at the Ujung Batu Timur Village Office and involving 23 participants. Post-training survey results show that most participants felt satisfied and benefited from this activity, with a satisfaction level of 80.45%. This program is expected to contribute to the development of micro-enterprises and improve the welfare of the local community.